Geoquímica de los elementos traza en las vulcanitas del Cenozoico Superior de la región central de Costa Rica - Paniagua Pérez, Sergio (2011)
This paper presents new analysis of trace elements (Co, Cu, Ni, Rb, Sr, Zr, Y, Nb, Ce, La, Ba, Zn), in the basalts of the pliocene Aguacate Group of the "Valle Central" and the cuaternary ptoducts of the strato-voIcanes of the "Cordillera Central of Costa Rica. The preliminary geochemical characterization of those elements and the diverse variation diagrams suggest an evolutionary magmatic tendency in the different types of rocks in the Central Region of the country, which begins with the most basic menbers of the cuaternary series (basalts) and end with the ashflows of intermediate to acidic composition, pointing out that the basics samples from the Aguacate Group are dispersed and apparently follow no evolution pattern, indicating they are rocks which possibly belong to another magmatic series. Also it is attempted to prove the location and classification of the basic menbers of the "Cordillera Central" serie of Costa Rica in the corresponding geotectonic setting, applying to them the various petrologic and tectonic diagrams of PEARCE and CANN (1973).